The Impact of GNI Per Capita on the Prevalence and Incidence of Anxiety and Depressive Disorders: A Global Analysis Using GBD 2023 Data - Dede Efendy; Utami Utami; Vita Widyasari; Yoga Saputra; Yuni Asnaini (Jurnal Kesehatan Amanah, 2026)
Mental health disorders, particularly depression and anxiety, remain major contributors to the global burden of disease and disability. Socioeconomic inequality, including differences in Gross National Income (GNI) per capita, is considered an important factor influencing mental health outcomes. This study aimed to analyze the relationship between GNI per capita and the prevalence of depression and anxiety disorders globally using data from the Global Burden of Disease (GBD) 2023 database. A descriptive ecological study design was conducted using secondary data from 187 countries and regions. Data were analyzed using descriptive statistics, Spearman correlation tests, and regional comparative analysis with ANOVA. The results showed substantial disparities in mental health burden and income distribution across regions. Africa had the highest average prevalence of depression, while Asia showed the greatest variability in anxiety disorders. A significant negative correlation was found between depression prevalence and income levels (r = -0.213; p = 0.003), indicating higher depression rates in lower-income countries. However, anxiety showed a weak and insignificant relationship with income (r = -0.079; p = 0.281). These findings emphasize the need to reduce socioeconomic inequalities and strengthen mental health systems through integrated healthcare services and multisectoral policies.